REDUCTION OF GAS PORES AND NONMETALLIC IMPLEMENTS IN CASTINGS FROM 35XГСЛ AND 110Г13Л STEEL - N.M. Saidmakhamadov; V.B. Bekchanova; K.Kh. Abdullaev; N.X. Tadjiev; I.T. Tuxtaboev; M. N. Gaybullaev (Web of Journals Publishing, 2024)
A technology has been developed for producing high – quality foundry products with high physical and mechanical properties without non – metallic and gaseous pores by treating steel grades 35ХГСЛ and 110Г13Л with oxidizing elements in and outside the furnace.
Keywords: electric arc furnace, lining, alloy, flux, low – alloy steel, limestone, quartz sand, ferroalloy, ferromanganese, ferrosilicon, oxidation, reduction.